2018
DOI: 10.1038/s41431-018-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X-inactivation is common in the general female population

Abstract: X-inactivation is a well-established dosage compensation mechanism ensuring that X-chromosomal genes are expressed at comparable levels in males and females. Skewed X-inactivation is often explained by negative selection of one of the alleles. We demonstrate that imbalanced expression of the paternal and maternal X-chromosomes is common in the general population and that the random nature of the X-inactivation mechanism can be sufficient to explain the imbalance. To this end, we analyzed blood-derived RNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 42 publications
5
114
1
Order By: Relevance
“…Current results suggest that, in heterozygous carrier females, X‐inactivation status in blood and skin fibroblasts does not predict the clinical outcome. This is very much in line with results obtained for other X‐linked disease genes and also with recent findings suggesting that skewed X‐inactivation is common in the general female population (Shvetsova et al, ). Still, the variable clinical manifestations of heterozygous carrier females with a de novo variant ranging from very mildly to severely affected may be partially explained by the X‐inactivation status within specific affected cells and tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Current results suggest that, in heterozygous carrier females, X‐inactivation status in blood and skin fibroblasts does not predict the clinical outcome. This is very much in line with results obtained for other X‐linked disease genes and also with recent findings suggesting that skewed X‐inactivation is common in the general female population (Shvetsova et al, ). Still, the variable clinical manifestations of heterozygous carrier females with a de novo variant ranging from very mildly to severely affected may be partially explained by the X‐inactivation status within specific affected cells and tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Next, we focused on the molecular mechanism of skewed XCI of the normal X chromosome of patient 1. Studies of X inactivation patterns in general population demonstrated that only very small proportions (8% and 10%) of unaffected females show significantly skewed inactivation (<25:75/>75:25; Amos-Landgraf et al, 2006;Nesterova et al, 2003;Shvetsova et al, 2019). However, patients harboring Xq27.3q28 deletion, including the presented patient 1 of the current study, show relatively high ratios of skewed XCI of the normal allele (5/12).…”
Section: Discussioncontrasting
confidence: 50%
“…Men are the only ones who inherit Y-chromosome-linked genes, but both men and women can inherit X-chromosome-linked genes (Zhang et al 2017). X-chromosome inactivation is responsible for sex chromosome dosage compensation in females (XX) (Shvetsova et al 2019) that is the reason why males have worse symptoms than females. Males are more susceptible and have worse symptoms than females in ASD.…”
Section: The Interaction Of Gut Microbiota and Genetics Affects The Dmentioning
confidence: 99%